Problems and Prospects of Developing Rare Types of Tourism in the Arkhngelsk Region - Yu. Yu. Pavlova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the acute problems of social and economic development of the region, which affect the tourist sector and identifies causes of rising demand for internal travel. Niche types of tourism were researched. The author elaborated classification of resources necessary for rare types of travel and formulated key criteria required for their ranging. This classification includes all types of resources in view of their origin. The article investigates principle trends of rare types of tourism, puts forward the definition ‘dark types of tourism’, gives a list of resources included in this category and reveals aspects that have negative impact on resource potential of the territory. A list of objects was provided, whose inclusion in the program of traditional tours can raise competitiveness of new routes on travel service market and can become a key section of the excursion program oriented only to rare types of tourism. Vast resource potential of the country in general and the Arkhangelsk region, in particular, diversity of their natural and anthropogenic objects, unique phenomena gave an opportunity to the author to write that in case of skilled and efficient regional management deterrents for the development of rare types of tourism can be eliminated.